2018
DOI: 10.1007/s12105-018-0965-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute Invasive Fungal Rhinosinusitis: Frozen Section Histomorphology and Diagnosis with PAS Stain

Abstract: Acute invasive fungal rhinosinusitis (AIFRS) is a fulminant infection in immunocompromised patients requiring rapid diagnosis (DX), frequently made on frozen section (FS) of sinonasal biopsies, followed by prompt surgical debridement. However, FS interpretation is often difficult and DX sometimes not possible. In this study we sought to characterize reasons for misinterpretation and methods to improve diagnostic accuracy. The FS slides from 271 biopsies of suspected AIFRS in a 16-year period were reviewed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The endoscopic findings can be variable such as erosive, edematous, dry, or pale mucosa initially, and change to ulceration, necrosis, or suspected ischemia when advanced. 10,11 Biopsy should be performed at any abnormal region such as pale or darkened mucosa, ulcer, or crusted area on endoscopic examination. However, when high suspicion and sufficient risk factors exist, biopsy at endoscopically normal tissues might be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endoscopic findings can be variable such as erosive, edematous, dry, or pale mucosa initially, and change to ulceration, necrosis, or suspected ischemia when advanced. 10,11 Biopsy should be performed at any abnormal region such as pale or darkened mucosa, ulcer, or crusted area on endoscopic examination. However, when high suspicion and sufficient risk factors exist, biopsy at endoscopically normal tissues might be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, when high suspicion and sufficient risk factors exist, biopsy at endoscopically normal tissues might be considered. 11 The middle turbinate has been shown to be the most common site of fungal invasion (sensitivity of 75% to 86%, specificity of 100%). 14,15 Therefore, middle turbinate biopsy should…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that frozen sections, especially with PAS staining, 14 are a sensitive test for rhinocerebral mucormycosis 15 . While this has not been studied in colonic mucormycosis, there exists a potential for earlier confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Acute invasive fungal rhinosinusitis (AIFRS) is a lethal form of sinusitis with high morbidity and mortality, in immunocompromised patients and it needs a rapid diagnosis and treatment. A rapid and accurate diagnosis is crucial for the timely and effective treatment and prevention of complications 9 .…”
Section: Introductionmentioning
confidence: 99%